Modernism In Islamic Education In Tafsir Al-Manār: An Epistemological Review Of Muhammad Abduh And Muhammad Rashid Ridha - Gojali, M. Imam; Fauzi, Imron; Umam, Khotibul (Center of Language and Cultural Studies, 2024)
The decline of the Islamic world in the 18th century was triggered by complacency and rigid thinking, where Muslims understood religion blindly without deep understanding. The Western factor that dominated education in the Islamic world also contributed to this stagnation. Liberals see Western modernization as the key to the success of advanced civilization, especially in technology. This modernization, represented by the airplane, created an impetus for Muslims to pursue technological advancement. The Qur'an, as a universal guide for Muslims, must be interpreted according to the context of the times to remain relevant. Modernism brought disciplines such as economics, psychology, history, law, politics, and social sciences, which have a clear religious legal basis. Modernist thought emphasized the need for modern education in developing Islamic society. Muhammad Abduh, an Egyptian reformer, highlighted the inability of Muslims to build an advanced civilization. His thinking created a reformist project, placing Islamic education as the foundation for creating a modern and moral society. The modernization of Islamic education by figures such as Abduh and Rashid Ridha was geared towards achieving modern scientific advancement and competing on a global level. However, efforts to modernize Islamic education are not always successful. Some efforts, such as those made by Ziya Gokalp and Fazlur Rahman, are trapped in secularism or ineffective. This research uses a literature study method with a Historical-Philosophical and Empirical-Phenomenological approach. The findings show that the modernism of Islamic education in tafsir al-Manār by Muhammad Abduh and Rasyid Ridha involves reforms in curriculum, teaching staff, institutions, and teaching methods. This research contributes by digging deeper into the concept of modernism in Islamic education from a historical and philosophical point of view. As a response to social and cultural conditions, modernism in Islamic education is essential to build an Islamic civilization that is dynamic and relevant in the context of an ever-evolving era.